Excellent absorption properties of BaFe12−xNbxO19 controlled by multi-resonance permeability, enhanced permittivity, and the order of matching thickness. Issue 32 (8th August 2017) - Liu, Chuyang; Zhang, Yujing; Tang, Yu; Wang, Zongrong; Tang, Haichao; Ou, Yang; Yu, Le; Ma, Ning; Du, Piyi
Abstract : Correlations of multi-resonance permeability, enhanced permittivity, and the order of matching thickness to absorption properties are elaborately established, which provide guidance for the design of high-performance absorbing materials. Abstract : For the sol–gel-derived BaFe12− x Nb x O19 ( x = 0–0.6), coercivity ( H c ) and saturation magnetization ( M s ) vary from 3.53–0.85 kOe and 70.3–53.8 emu g −1 to 1.02–0.22 kOe and 69.6–59.5 emu g −1, respectively, with an increase in sintering temperature from 1250 °C to 1350 °C. Moreover, ε ′ and ε ′′ increase from 4.13–4.04 and 0.0049–0.0045 to 7.64–6.93 and 1.50–0.97 over 26.5–40 GHz, and the multi-resonance peaks in permeability shift from ∼40+ GHz to ∼27 GHz. The bandwidth (BW) and reflection loss peak intensity (RLp ) are broadened and enhanced from 0.8 GHz and −10.3 dB of the sample with x = 0.2 sintered at 1250 °C under 0.92 mm to 11.9+ GHz and −54 dB, respectively, of the sample with x = 0.6 sintered at 1350 °C under 0.86 mm around a millimeter-wave atmospheric window of 35 GHz. The effects of Nb 5+ content ( x ) and sintering temperature on grain size, phase compositions, formations of Fe 2+ and oxygen vacancy, and thus on static magnetism and EM parameters are investigated. The correlations of multi-resonance permeability, enhanced permittivity, and the order of matching thickness with absorption properties are also discussed in detail.